Firm Size and the Information Content of Over-the-Counter Common Stock Offerings - Robert M. Hull; George E. Pinches (Journal of Small Business Finance, 1995)
We examine the announcement period of stock returns for 179 over-the-counter (OTC) firms that issue common stock to reduce nonconvertible debt. We find that small OTC firms experience returns that are significantly more negative than large OTC firms. Regression tests reveal that firm size is a significant factor in accounting for stock returns. Other tests establish as firm size a dominant effect. Our support for a firm size effect is consistent with a differential information effect given that firm size is positively related to the amount of information available about firms.
Keywords: L25; G14; G32; 650; Firm Size; Information; OTC; Stock Offerings; Stock